Analysis of Calculation, Withdrawal and Reporting of Income Tax Article 23 For Cleaning Services at PT. Pelindo I Belawan Branch - Junawan; Anis Dary Arinto (Yayasan Multidimensi Kreatif, 2023)
The purpose of writing this final assignment is to find out whether calculating, withholding and reporting PPh Article 23 for cleaning services at PT. Pelindo I Belawan Branch in accordance with Law no. 36 of 2008. The data collection methods used in preparing this final assignment are secondary and primary methods. The research was conducted at PT. Pelindo I Belawan Branch. The data analysis technique in this research is descriptive qualitative. Cleaning services are one of the services that are subject to withholding from Income Tax Article 23 in accordance with Law no. 36 of 2008 concerning income tax. The imposition of the Article 23 Income Tax withholding rate which is withheld by PT. Pelindo I Belawan Branch is 2% of the gross amount. Because ISS Indonesia as the service vendor has a NPWP. The results of the research are that the imposition of Income Tax Article 23 on cleaning services provided by PT. Pelindo I Belawan Branch is in accordance with Law no. 36 of 2008.